The Effectiveness of Guided Inquiry-Based on Nuclear Physics Learning Devices with PhET Media to Increase Student Creativity - Susilawati Susilawati; Aris Doyan; Syahrial Ayub; Wahyudi Wahyudi; Jannatin 'Ardhuha; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to test the effectiveness of developing core physics learning tools using an inquiry model with the help of PhET media in increasing student creativity. The development of the learning device uses a 4D model consisting of define, design, develop and disseminate. The sample of this research is all undergraduate students who take nuclear physics courses, totaling 50 people. The sample consisted of two classes, namely class A as the experimental class and class B as the control class. The pre-test and post-test data were analyzed using the t-test at a significant level of 5%, while the increase in student creativity was analyzed using the N-gain test. The results of the t-test show that the t-count value is greater than the t-table, which means that the nuclear physics learning device using an inquiry model with the help of PhET media affects student creativity. The results of the N-gain analysis show that the experimental class is in the high category, while the control class is in the medium and low category. These results indicate that the use of nuclear physics learning tools using an inquiry model with the help of PhET media is effective in increasing student creativity